Chaos - Pierce, Michael (Michael A.); Giglio, Tony; Jones, Huw Penallt; Wilding, Gavin; Derbas, Michael; Statham, Jason, 1967-; Phillippe, Ryan, 1974-; Snipes, Wesley; Waddell, Justine; Czerny, Henry; Capitol Films; Chaotic Productions Ltd.; et al. (Santa Monica, CA : Lionsgate, 2008)
After a deadly bank heist, Detectives Quentin Conners and Shane Dekker are drawn into a mysterious case where nothing is what it seems. Pulling the strings is a criminal mastermind who seems to kill without warning or reason. Abound with random acts of violence and deception, the only hope for survival is finding an order to the chaos.
Title from container.
Originally released as a motion picture in 2005.
Special features: Commentary with director Tony Giglio; "The order behind 'Chaos'" featurette.
Director of photography, Richard Greatrex ; editor, Sean Barton ; music, Trevor Jones ; costume designer, Bobbie Read ; production designer, Chris August.
Jason Statham, Ryan Phillippe, Wesley Snipes, Justine Waddell, Henry Czerny.
MPAA rating: R; violence and language.
Keywords: Bank robberies -- Drama; Murder -- Drama; Detectives -- Drama; Criminal investigation -- Drama; Chaotic behavior in systems -- Drama; Computer viruses -- Drama; Feature films; Action and adventure films; Thrillers (Motion pictures); Thrillers (Television programs); Police films; Video recordings for the hearing impaired; Thriller -- Feature; Police -- Feature; Crime -- Feature; Feature films; Suspense films; Action and adventure films